Video-letter as a methodology in the field of mental healthcare La rara troupe and Locamente as case studies in two art museums - Sola, Belén (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2023)
This article shows video-letter as a creative tool from the studies of two long term projects that have been developed with people with mental health issues in the Contemporary Art Museum of Castilla y León (León) and in the Domus Artium Art Centre (Salamanca). In the first one, based on the project “La rara troupe” and in the second one from the project “Locamente”. The article explains how the video-letter, as an audiovisual and educational tool, aims the articulation of the groups from the negotiation of the individual subjectivities that are involved in the projects, provoking with this method not only intra communication but inter communication too, based on audiovisual creativity. At last, the article proposes “La rara troupe” as a prototype of a project that might be replicated in other communities aiming to think about health care and creativity from a particular point of view based on the experiences of people directly involved in these issues. And at the same time understanding diversity as a concept that helps to avoid labels and stereotypes about mental illnesses, foster new ways to build understanding and transformation in our social contexts.